2013
DOI: 10.1186/1471-2407-13-25
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a is a tumor suppressor in choriocarcinoma via regulation of Delta-like1

Abstract: BackgroundChoriocarcinoma is a gestational trophoblastic tumor which causes high mortality if left untreated. MicroRNAs (miRNAs) are small non protein-coding RNAs which inhibit target gene expression. The role of miRNAs in choriocarcinoma, however, is not well understood. In this study, we examined the effect of miR-34a in choriocarcinoma.MethodsMiR-34a was either inhibited or ectopically expressed transiently in two choriocarcinoma cell lines (BeWo and JEG-3) respectively. Its actions on cell invasion, prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 45 publications
0
32
1
Order By: Relevance
“…In addition, forced expression of miR-34a suppressed the invasiveness of HeLa and JAR cells, which was attributed to the regulation of expression of urokinase plasminogen activator through Notch (Pang et al, 2010). More recently, they observed that miR-34a reduced cell proliferation and invasiveness, at least, partially through its inhibitory effect on DLL1 in choriocarcinoma (Pang et al, 2013). Our pilot study with microarray revealed that the DLL1 expression in resistant H69AR cells was significantly lower than that in sensitive H69 cells.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, forced expression of miR-34a suppressed the invasiveness of HeLa and JAR cells, which was attributed to the regulation of expression of urokinase plasminogen activator through Notch (Pang et al, 2010). More recently, they observed that miR-34a reduced cell proliferation and invasiveness, at least, partially through its inhibitory effect on DLL1 in choriocarcinoma (Pang et al, 2013). Our pilot study with microarray revealed that the DLL1 expression in resistant H69AR cells was significantly lower than that in sensitive H69 cells.…”
Section: Discussionmentioning
confidence: 61%
“…Data about elevated mTORC1-activation in numerous solid tumours and lymphomas are increasing. Our experimental and in vivo xenograft results suggest that the addition of rapalogues to treatment protocols could be beneficial not only in mantle cell lymphomas (MCLs) but also in other lymphomas with high mTORC1 activity -such as Hodgkin lymphomas, non-germinal center type diffuse large B-cell lymphomas and acute lymphoblastic leukemias [24,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 95%
“…mTOR activity related phosphorylated proteins (p-mTOR, p-p70S6K, p-4EBP1 and p-S6) were detected in biopsies of Burkitt-lymphoma patients [24] and in HT58 lymphoma xenografts, which suggests that enhanced mTOR signalling activity is present in vivo (Supplemented Figure), which may serve as a potential therapeutic target. To prove the in vivo relevance of our observations, mice with HT58 lymphoma xenografts were treated with low dose Rapamune.…”
Section: Rapamycin Treatment Inhibits Proliferation and Induces Apoptmentioning
confidence: 94%
“…Analytical proteins included P53 [6,7] and CMYC [8,9] (oncogene related); Ki67 (proliferation related); BCL-2 [10,11] (apotosis related); NM23 [12] (metastasis related); E-calrentin and β-catenin (adhesion related); CDK4 [13] and Cyclin1 [14] (cell cycle related); VEGR (angiogenesis related), GST [15], COX-2 [16], MDM2 [17], and TS (drug related); and EBV [18] (virus related).…”
Section: Immunohistochemical Analysis Of Protein Expression Of Known mentioning
confidence: 99%